Chaperone patterns in vernal keratoconjunctivitis are distinctive of cell and Hsp type and are modified by inflammatory stimuli. Issue 3 (23rd December 2015) - Leonardi, A.; Tarricone, E.; Corrao, S.; Alaibac, M.; Corso, A. J.; Zavan, B.; Venier, P.; Conway de Macario, E.; Macario, A. J. L.; Di Stefano, A.; Cappello, F.; Brun, P.
Abstract: Background: Vernal keratoconjunctivitis (VKC) is a severe ocular allergy with pathogenic mechanism poorly understood and no efficacious treatment. The aims of the study were to determine quantities and distribution of Hsp chaperones in the conjunctiva of VKC patients and assess their levels in conjunctival epithelial and fibroblast cultures exposed to inflammatory stimuli. Methods: Hsp10, Hsp27, Hsp40, Hsp60, Hsp70, Hsp90, Hsp105, and Hsp110 were determined in conjunctiva biopsies from nine patients and nine healthy age‐matched normal subjects, using immunomorphology and qPCR. Conjunctival epithelial cells and fibroblasts were cultured and stimulated with IL‐1β, histamine, IL‐4, TNF‐α, or UV‐B irradiation, and changes in Hsp levels were determined by Western blotting. Results: Hsp27, Hsp40, Hsp70, and Hsp90 levels increased in the patients' conjunctiva, whereas Hsp10, Hsp60, Hsp100, and Hsp105 did not. Double immunofluorescence demonstrated colocalization of Hsp27, Hsp40, Hsp70, and Hsp90 with CD68 and tryptase. Testing of cultured conjunctival cells revealed an increase in the levels of Hsp27 in fibroblasts stimulated with IL‐4; Hsp40 in epithelial cells stimulated with IL‐4 and TNF‐α and in fibroblasts stimulated with IL‐4, TNF‐α, and IL‐1β; Hsp70 in epithelial cells stimulated with histamine and IL‐4; and Hsp90 in fibroblasts stimulated with IL‐1β, TNF‐α, and IL‐4. UV‐B did not induce changes. Conclusions: VKC conjunctiva displays distinctive quantitative patterns of Hsps as compared with healthy controls. Cultured conjunctival cells respond to cytokines and inflammatory stimuli with changes in the Hsps quantitative patterns. The data suggest that interaction between the chaperoning and the immune systems drives disease progression.